Sarcobesity, but not visceral fat, is an independent risk factor for complications after radical resection of colorectal cancer - Feng, Zhewen; Pang, Kai; Tian, Mingwei; Gu, Xiaozhe; Lin, Huajun; Yang, Xiaobao; Yang, Yingchi; Zhang, Zhongtao (Frontiers in Nutrition, 2023)
Background The influence of body composition on the outcome of colorectal cancer surgery is controversial. The aim of this study was to evaluate the effects of visceral obesity and sarcobesity on the incidence of total and surgical complications after radical resection of colorectal cancer. Methods We collected a total of 426 patients who underwent elective radical resection of colorectal cancer at Beijing Friendship Hospital, Capital Medical University from January 2017 to May 2018. According to the inclusion and exclusion criteria, 387 patients were finally included. A CT scan at the level of the L3-L4 intervertebral disk was selected to measure the values of visceral fat area and skeletal muscle area. Multivariate analysis was used to explore the independent risk/protective factors affecting postoperative complications. Results 128 (33.1%) patients developed complications, and 44 (11.4%) patients developed major complications. Among them, 111 patients developed surgical complications and 21 developed medical complications. Visceral fat area (Z = −3.271, p = 0.001), total fat area (Z = −2.613, p = 0.009), visceral fat area to subcutaneous fat area ratio (V/S, Z = −2.633, p = 0.008), and sarcobesity index (Z = −2.282, p = 0.023) were significantly associated with total complications. Visceral fat area (Z = −2.119, p = 0.034) and V/S (Z = −2.010, p = 0.044) were significantly associated with total surgical complications. Sarcobesity index, smoking, stoma, blood loss, surgery time, and American Society of Anesthesiology (ASA) score were selected as risk factors for total postoperative complications according to LASSO regression. Multivariate logistic regression analysis suggested that sarcobesity index was an independent risk factor for postoperative total complications and surgical complications. Subgroup analysis suggested that albumin level was an independent protective factor for postoperative total complications in male patients. Smoking, operative time, and sarcobesity index were independent risk factors, and cholesterol was an independent protective factor for total postoperative complications in female patients. Conclusion Increased sarcobesity index is an independent risk factor for postoperative complications in patients with colorectal cancer, while visceral fat area is not. For female patients, smoking, operation time, and obesity index are independent risk factors for postoperative complications, while cholesterol is an independent protective factor. For male patients, serum albumin is an independent protective factor for postoperative complications.